Quantitative Structure-Activity Relationship Study of Fatty Acid Derivatives as Lubricant Additive - Sugesti, Rahmawita; Sutriah, Komar; Khotib, Mohammad (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Fatty acid compounds and their derivatives have been known in tribology as a source of bio-lubricant raw materials. New compounds were developed computationally to sort out the physical properties of the desired lubricant additive before synthesis in the laboratory. In this study, the correlation between the chemical structure of fatty acid derivative compounds and their physical properties through the quantitative structure-activity relationship (QSAR) using the density functional theory (DFT) was determined. QSAR model resulted in two linear regression equations for the wear rate performance test at (1) the value of the weld load with 5%, 500N variation and (2) the value of the wear scar diameter 5%, 150N variation. Validation of the regression model was conducted using the leave-one-out (LOO) method. The new additive lubricants were designed using the obtained QSAR models of the wear rate performance test with the descriptor of total energy, dipole moment, and softness. Stearoyl diethanolamine compound was proposed as a lubricant additive with the best performance parameter of weld load and wear scar diameter at 298.03 kg and 0.29 mm respectively. The percentage performance of stearoyl diethanolamine for weld load and wear scar diameter was increased by 24.18% and 47.60%, respectively.